Hyperacute vestibular syndrome: the role of an acute vertigo service - Bierrum, William; Haider, Salman; Balaratnam, Michelle; Alim-Marvasti, Ali; Chandratheva, Arvind; Simister, Robert; Koohi, Nehzat; Kaski, Diego (Frontiers in Stroke, 2023)
Differentiating between peripheral and central causes of acute vertigo remains a clinical obstacle in the acute setting. Despite the availability of several validated diagnostic paradigms, the take-up of such diagnostic tools is low because these tests are often unfamiliar to most emergency physicians. Embedding an acute vertigo service within the emergency setting can help improve the diagnostic workup of patients presenting with acute vertigo and have significant economic benefits, including admission avoidance, reduce unnecessary investigations and decrease length of hospital stay. In this paper, we present four patients who were referred to the acute vertigo service at University College London Hospital (UCLH) for review. We discuss indications and limitations to the implementation of such a service.